Deciphering the World of eSports. Issue 1 (2nd January 2020) - Scholz, Tobias M.
ABSTRACT: This editorial gives a short preface to the eSports industry and why this industry is unusual for media management research – thereby describing the eSports ecosystem based on the stakeholders involved, the fundamental characteristics, and the governing principles of the industry. Then the three papers in this special issue are introduced. These papers show the uniqueness of the eSports industry by enhancing the understanding of eSports in a media management context. Furthermore, the editorial is highlighting its potential contribution to the field in aspects like the changing role of the consumers having a stronger influence on the media process, moving from global to local, and online to offline or the changes in media engagement in a digital environment. The editorial concludes by stating the potential of researching eSports as a case for the path to digitize media management and, additionally, create sustainable business models in the digitized society.